2021
DOI: 10.1038/s41467-021-25713-1
|View full text |Cite
|
Sign up to set email alerts
|

Glycan remodeled erythrocytes facilitate antigenic characterization of recent A/H3N2 influenza viruses

Abstract: During circulation in humans and natural selection to escape antibody recognition for decades, A/H3N2 influenza viruses emerged with altered receptor specificities. These viruses lost the ability to agglutinate erythrocytes critical for antigenic characterization and give low yields and acquire adaptive mutations when cultured in eggs and cells, contributing to recent vaccine challenges. Examination of receptor specificities of A/H3N2 viruses reveals that recent viruses compensated for decreased binding of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(105 citation statements)
references
References 53 publications
4
101
0
Order By: Relevance
“…For H3N2 viruses, the amino acid substitutions at positions 190, 226, and 194 of HA were associated with the loss of the ability for the A(H3N2) viruses to agglutinate chicken erythrocytes [ 234 , 236 239 ]. Since the 2004–2005 influenza season, A(H3N2) viruses acquired Asp225Asn in HA, which caused the loss of their binding abilities to turkey erythrocytes [ 227 , 230 ]; this may be attributed to the inability of viral binding to short oligosaccharides terminated with sialic acids (i.e., those having only one or two N-acetyl-lactosamine repeating units), which are mainly expressed by chicken or turkey erythrocytes [ 240 ]. As an extreme example, a large portion of A(H3N2) viruses, especially clade 3C.2a viruses, have lost the capacity to agglutinate chicken, turkey, and guinea pig erythrocytes [ 229 , 241 ]; thus, they cannot be antigenically characterized by HI assays.…”
Section: Influenzamentioning
confidence: 99%
“…For H3N2 viruses, the amino acid substitutions at positions 190, 226, and 194 of HA were associated with the loss of the ability for the A(H3N2) viruses to agglutinate chicken erythrocytes [ 234 , 236 239 ]. Since the 2004–2005 influenza season, A(H3N2) viruses acquired Asp225Asn in HA, which caused the loss of their binding abilities to turkey erythrocytes [ 227 , 230 ]; this may be attributed to the inability of viral binding to short oligosaccharides terminated with sialic acids (i.e., those having only one or two N-acetyl-lactosamine repeating units), which are mainly expressed by chicken or turkey erythrocytes [ 240 ]. As an extreme example, a large portion of A(H3N2) viruses, especially clade 3C.2a viruses, have lost the capacity to agglutinate chicken, turkey, and guinea pig erythrocytes [ 229 , 241 ]; thus, they cannot be antigenically characterized by HI assays.…”
Section: Influenzamentioning
confidence: 99%
“…Another study also suggested that recent H3N2 viruses exhibit increased recognition of complex sialylated N-glycans and non-sialylated phosphorylated high-mannose glycans [72]. The changes in glycan binding specificities in sialylated glycans are likely due to substitutions in the receptor-binding sites of virus HA caused by antigenic drift [69,71,73].…”
Section: Sialylated N-glycans Receptorsmentioning
confidence: 94%
“…Another study also suggested that recent H3N2 viruses exhibit increased recognition of complex sialylated Nglycans and non-sialylated phosphorylated high-mannose glycans [72]. The changes in glycan binding specificities in sialylated glycans are likely due to substitutions in the receptor-binding sites of virus HA caused by antigenic drift [69,71,73]. Only a few studies have been conducted in which Neu5Gc, a common form of Sia, acts as an influenza virus receptor [61][62][63][64][65][66], while most studies have focused on Neu5Ac.…”
Section: Sialylated N-glycans Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggest that human IAV strains preferentially bound to long branched sialoglycans with poly-lactosamine (polyLN) repeats that had an ‘umbrella-like’ topology, whereas avian IAV strains preferentially bound to short sialoglycans with a single lactosamine that had a ‘cone-like’ topology, indicating that glycan topology can also determine host range (Chandrasekaran et al, 2008). In agreement, circulating human H3N2 viruses have evolved to utilize extended branched polyLN glycans (N-glycans), while the parental pandemic H3N2 strain preferentially bound to short sialyl-LN glycans (Broszeit et al, 2021; Byrd-Leotis et al, 2019a; Peng et al, 2017). In array slides, glycans are immobilized in non-natural configurations at a high density with uniformity and hence, the conclusions can be biased on the repertoire of glycans presented (Raman et al ., 2014; Shi et al ., 2014).…”
Section: Introductionmentioning
confidence: 97%